The effect of magnesium on mitotic spindle formation in Schizosaccharomyces pombe - Uz,Gulsen (2016)
Abstract Magnesium (Mg2+), an essential ion for cells and biological systems, is involved in a variety of cellular processes, including the formation and breakdown of microtubules. The results of a previous investigation suggested that as cells grow the intracellular Mg2+ concentration falls, thereby stimulating formation of the mitotic spindle. In the present work, we used a Mg2+-deficient Schizosaccharomyces pombe strain GA2, in which two essential membrane Mg2+ transporter genes (homologs of ALR1 and ALR2 in Saccharomyces cerevisae) were deleted, and its parental strain Sp292, to examine the extent to which low Mg2+ concentrations can affect mitotic spindle formation. The two S. pombe strains were transformed with a plasmid carrying a GFP-α2-tubulin construct to fluorescently label microtubules. Using the free Mg2+-specific fluorescent probe mag-fura-2, we confirmed that intracellular free Mg2+ levels were lower in GA2 than in the parental strain. Defects in interphase microtubule organization, a lower percentage of mitotic spindle formation and a reduced mitotic index were also observed in the GA2 strain. Although there was interphase microtubule polymerization, the lower level of mitotic spindle formation in the Mg2+-deficient strain suggested a greater requirement for Mg2+ in this phenomenon than previously thought.